The Impact of Working Capital Management, Capital Structure, and Financial Planning on Micro Business Profitability in MSMEs Receiving the KUR Program in Surabaya City - Warcono, Tri (West Science Journal Economic and Entrepreneurship, 2025)
This study investigates the impact of working capital management, capital structure, and financial planning on the profitability of micro businesses participating in the Kredit Usaha Rakyat (KUR) program in Surabaya City. Using a quantitative explanatory research design, data were collected from 160 micro business owners who met the criteria of active KUR recipients for at least one year. The research employed Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the proposed hypotheses. The results show that capital structure has the strongest positive and significant effect on micro business profitability, followed by working capital management and financial planning. Furthermore, the findings reveal that these financial management practices are interrelated, with each construct contributing uniquely to profitability improvement. The study underscores the importance of integrated financial strategies for micro entrepreneurs to enhance operational efficiency, optimize resource allocation, and maintain financial stability. These insights provide valuable implications for policymakers, financial institutions, and business practitioners in designing targeted interventions to strengthen the sustainability and competitiveness of micro enterprises in Indonesia.